Childhood Adversity and Developmental Effects 2015
DOI: 10.1201/b18372-16
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversity, Recent Life Stressors and Suicidal Behavior in Chinese College Students

Abstract: Background: Development policymakers and child-care service providers are committed to improving the educational opportunities of the 153 million orphans worldwide. Nevertheless, the relationship between orphanhood and education outcomes is not well understood. Varying factors associated with differential educational attainment leave policymakers uncertain where to intervene. This study examines the relationship between psychosocial well-being and cognitive development in a cohort of orphans and abandoned chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…PHIV in particular, live with elevated levels of depressive symptoms and distress, more than exposed controls and unexposed controls. Thus, we confirm previous reports in children with PHIV that high levels of psychosocial distress, and not HAART, predicted sub-optimal development [ 18 ]. Hence, the long-term benefit of HAART in PHIV may be moderated by psychosocial distress, high levels of depressive symptoms, low esteem and low levels of positive outlook.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PHIV in particular, live with elevated levels of depressive symptoms and distress, more than exposed controls and unexposed controls. Thus, we confirm previous reports in children with PHIV that high levels of psychosocial distress, and not HAART, predicted sub-optimal development [ 18 ]. Hence, the long-term benefit of HAART in PHIV may be moderated by psychosocial distress, high levels of depressive symptoms, low esteem and low levels of positive outlook.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of psychiatric disorders in PHIV children from the United States ranges from 55 to 61% [ 15 ] and PHIV were four times more likely to develop psychiatric disorders relative to unexposed controls who were US children [ 16 , 17 ]. A study of early versus delayed HAART in children with HIV from five low-income countries found that high levels of psychosocial distress, not HAART, predicted poor cognitive outcomes in older PHIV children [ 18 ] and suggests the importance of understanding psychosocial adjustment (PA) in HIV-affected children. Healthy PA is associated with low stress levels in children and enhances quality of life throughout the life-course [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It reinforces as well as challenges some of many documented facts about OVCs‐HIV. This study was in agreement with findings from literature that OVCs‐HIV are at increased risk for psychological problems (Atwine, Cantor‐Graae, & Bajunirwe, ; AVERT, ; Escueta et al, ; King, De Silva, Stein, & Patel, ; Lee et al, ), and the focus group discussions further added to these by describing the impecunious environment that helps creates them. Focus groups especially emphasized psychological issues for girls manifesting as “stress” due to monetary issues, taking on adult responsibility and lack of age appropriate socialization and respect.…”
Section: Discussionsupporting
confidence: 90%
“…An abnormal score identifies likely “cases” with mental health issues. The youth‐report version of the SDQ has been used in studies in Kenya as well as several other countries of sub‐Saharan Africa (Escueta, Whetten, Ostermann, O'Donnell, & POFO Research Team, ; Kashala, Elgen, Sommerfelt, & Tylleskar, ; Puffer et al, ). No studies have comprehensively evaluated the psychometric properties of the SDQ in these communities (Hoosen, Davids, de Vries, & Shung‐King, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter items were cognitively tested and refined iteratively in a sample of ~ 40 children and 20 school staff members from Kampala primary schools to ensure understanding and that meanings of original items were adequately captured. They then surveyed a larger sample of 697 children and 40 staff from Kampala schools to test distributions of items and to test study procedures Cut-off scores used were highest decile formed the ‘high difficulties’, the next decile formed ‘medium difficulties’ and the remaining 80% formed the ‘low difficulties’ Has not used UK cut-off scores to make comparisons TDS = .70 For girls exposure to physical violence in the past week was associated with higher levels of poor mental health using the SDQ Escueta (2014) [ 47 ] Ethiopia, Kenya, Tanzania, India, Cambodia 6–12 Examined relationship between psychosocial well-being and cognitive development orphans and abandoned children (OAC) relative to non-OAC in 5 LMICs to understand factors associated with success in learning Orphans, psychosocial well-being, cognitive development Self-report, parent 1480 orphaned and abandoned children Not specified None mentioned Did not apply any cut-off scores Has not used UK cut-off scores to make comparisons Overall alpha score reported = .73 An increase in emotional difficulties was found to be associated with delays in cognitive development Lachman (2014) [ 48 ] KwaZulu-Natal, South Africa 10–17 Examined the relationship between HIV/AIDS and positive parenting HIV/AIDS, parenting Parent 685 parent–child dyads with AIDS-ill caregiver and 184 caregiver-child dyad orphaned by AIDS isiZulu Translated into isiZulu and back-translated into English Did not apply any cut-off scores Has not used UK cut-off scores to make comparisons TDS = .71 Families who had caregivers who had AIDS or AIDS-orphaned children were significantly related to less positive parenting, higher poverty, higher depression and higher child total difficulties when compared to non-affected families Marais (2014) [ 49 ] Mangaung, South Africa 7–11 …”
Section: Methodsmentioning
confidence: 99%